Goal-directed self-talk interventions: A single-case study with an elite athlete - Latinjak, A. T.; Font-Llado, R.; Zourbanos, N.; Hatzigeorgiadis, A. (The Sport Psychologist, 2016)
The purpose of this single-case study was to describe a goal-directed self-talk (ST) intervention with an elite athlete. The participant was a 36-year-old elite orienteerer, who declared himself to be continuously engaged in some sort of autonomous self-dialogue. During six sessions, we undertook an intervention which started with identifying variety of relevant problematic sport situations and goal-directed ST in them. Subsequently, through questioning, the original ST was challenged and alternative instructions were theoretically examined before putting them into practice. The participant valued highly the intervention process and its outcomes. Overall, the study provides preliminary evidence on the effectiveness of goal-directed ST interventions and encourages research to further explore their potential. ABSTRACT FROM AUTHOR